2019
DOI: 10.1016/j.bbrc.2019.01.070
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblast β2 adrenergic signaling amplifies cardiac hypertrophy in mice

Abstract: Abnormal β-adrenergic signaling plays a central role in human heart failure. In mice, chronic β-adrenergic receptor (βAR) stimulation elicits cardiac hypertrophy. It has been reported that cultured cardiac fibroblasts express βAR; however, the functional in vivo requirement of βAR signaling in cardiac fibroblasts during the development of cardiac hypertrophy remains elusive. β2AR null mice exhibited attenuated hypertrophic responses to chronic βAR stimulation upon continuous infusion of an agonist, isoprenalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Many previous reports have demonstrated that IL‐6/IL‐6R signaling induces cardiac remodeling including myocardial hypertrophy 2,23,24 . In addition, we have recently reported that β2AR KO mice ameliorated cardiac hypertrophy and dysfunction induced by continuous ISO stimulation and that constitutive activation of PKA in fibroblasts resulted in cardiac hypertrophy 10 . Taken together with this study, it is possible that β2‐adrenergic stimulation increases IL‐6 release from CFs, contributing to forming cardiac remodeling.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Many previous reports have demonstrated that IL‐6/IL‐6R signaling induces cardiac remodeling including myocardial hypertrophy 2,23,24 . In addition, we have recently reported that β2AR KO mice ameliorated cardiac hypertrophy and dysfunction induced by continuous ISO stimulation and that constitutive activation of PKA in fibroblasts resulted in cardiac hypertrophy 10 . Taken together with this study, it is possible that β2‐adrenergic stimulation increases IL‐6 release from CFs, contributing to forming cardiac remodeling.…”
Section: Discussionsupporting
confidence: 76%
“…These results suggested that βAR signaling predominantly upregulated IL‐6. Adult murine CFs mainly expressed β2AR and β3AR, but not β1AR 10 . Thus, we investigated which subtype of βAR was responsible for IL‐6 upregulation in response to ISO (Figure 2A‐C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, to determine the myofibroblast-specific requirement of OASIS in fibrotic kidneys, we generated myofibroblastrestricted OASIS conditional knockout (OASIS cKO) mice using myofibroblast Postn promoter-driven Cre-loxP recombination system ( Figure 9A). 22 First, it was confirmed that the Postn promoter drives Cre recombinase protein expression within cells in renal interstitial fibrotic areas and in glomeruli of OASIS cKO mice Day 7 after UUO ( Figure S9), however, Cre protein is undetectable in WT kidneys. Moreover, the expression of OASIS/Creb3l1 mRNA was dramatically decreased in UUO-kidney and isolated myofibroblasts of OASIS cKO mice following Cre/loxP recombination ( Figure 9B,C).…”
Section: Oasis Ablation Resulted In Resistance To Kidney Fibrosismentioning
confidence: 74%
“…Cardiac hypertrophy, characterized by an increase in cell size to maintain cardiac output, can be caused by a variety of pathological stimuli, such as long‐term hypertensive stress, myocardial injury, and adrenergic stimulus overactivation (Imaeda et al, 2019; Shimizu & Minamino, 2016). However, sustained cardiac hypertrophy has been reported as a risk factor for heart failure (Camici et al, 2020), malignant arrhythmia (Liaquat & Makaryus, 2020), sudden death (Shenasa & Shenasa, 2017), and other serious consequences.…”
Section: Introductionmentioning
confidence: 99%